2004
DOI: 10.1152/ajplung.00108.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mucins and their O-Glycans from human bronchial epithelial cell cultures

Abstract: A longstanding question in obstructive airway disease is whether observed changes in mucin composition and/or posttranslational glycosylation are due to genetic or to environmental factors. We tested whether the mucins secreted by second-passage primary human bronchial epithelial cell cultures derived from noncystic fibrosis (CF) or CF patients have intrinsically different specific mucin compositions, and whether these mucins are glycosylated differently. Both CF and non-CF cultures produced MUC5B, predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 57 publications
6
68
1
1
Order By: Relevance
“…3A), suggesting that the concentration of mucus, rather than the source, was the critical variable. These data are consistent with previous data demonstrating no differences in the biochemical properties between the CF vs. normal mucins, the major component of mucus (20).…”
supporting
confidence: 93%
“…3A), suggesting that the concentration of mucus, rather than the source, was the critical variable. These data are consistent with previous data demonstrating no differences in the biochemical properties between the CF vs. normal mucins, the major component of mucus (20).…”
supporting
confidence: 93%
“…This channel has been linked to the regulation of mucus by controlling the production and/or release of secreted proteins such as Muc5ac, a major component of mucus found in the lung. 49 Recent studies have shown that by blocking the production and/or activity of mClca3 (or the human counterpart hClca1) inhibited the production of mucus, whereas overexpression of hClca1 enhanced mucus production. 42 These studies suggest that mClca3 plays a pivotal role in the production and/or regulation of mucus although the mechanics of this relationship have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric BAL fluid, sputum, and cell culture mucus samples were loaded at a constant volume (usually 30 μl, undiluted) onto a 0.7% agarose gel in a 1X Tris-acetate-EDTA (TAE) buffer with 1% SDS and electrophoresed in a horizontal gel apparatus as previously described (42). After electrophoresis, the gel was reduced in 10 mM DTT for 20 minutes prior to vacuum transfer onto a nitrocellulose membrane.…”
Section: Immunological and Physical Measurements Of Mucin Properties mentioning
confidence: 99%